2019
DOI: 10.3390/polym11111858
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Carbon-Based Buffer Layers for Polymer Solar Cells

Abstract: Carbon-based materials are promising candidates as charge transport layers in various optoelectronic devices and have been applied to enhance the performance and stability of such devices. In this paper, we provide an overview of the most contemporary strategies that use carbon-based materials including graphene, graphene oxide, carbon nanotubes, carbon quantum dots, and graphitic carbon nitride as buffer layers in polymer solar cells (PSCs). The crucial parameters that regulate the performance of carbon-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 113 publications
(138 reference statements)
0
10
0
2
Order By: Relevance
“… Main carbon-based structures studied against enveloped positive-sense single-stranded RNA viruses: (a) Graphite. Reprinted in part with permission under a Creative Commons CC BY 4.0 License from ref ( 133 ). Copyright 2019 MDPI.…”
Section: Antiviral Properties Of Carbon-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“… Main carbon-based structures studied against enveloped positive-sense single-stranded RNA viruses: (a) Graphite. Reprinted in part with permission under a Creative Commons CC BY 4.0 License from ref ( 133 ). Copyright 2019 MDPI.…”
Section: Antiviral Properties Of Carbon-based Materialsmentioning
confidence: 99%
“…(c) Multiwall carbon nanotubes. Reprinted in part with permission under a Creative Commons CC BY 4.0 License from ref ( 133 ). Copyright 2019 MDPI.…”
Section: Antiviral Properties Of Carbon-based Materialsmentioning
confidence: 99%
“…as interlayers in solar cells. [162,163] Ku et al [164] first reported the use of a carbon material in PSCs in which carbon/graphite was applied as a counter electrode for fully printable solar cells. Recently, fluorescent carbon dots (CDs) were incorporated by Jin et al [24] in the mesoporous TiO 2 interlayer for enhancing the photostability and performance of PSCs devices.…”
Section: Carbon and Graphene Qdsmentioning
confidence: 99%
“…In this respect, carbon-based materials, such as graphitic carbon nitride, carbon quantum dots, carbon nanotubes (CNTs) and graphene ( Jeon et al, 2018b ; Nguyen et al, 2019 ; Ouyang, 2019 ; Hu et al, 2020 ; Pan et al, 2020 ; Qin et al, 2020 ; Subramanyam et al, 2020 ; Shin et al, 2021 ; Vercelli, 2021 ), have attracted considerable research attention due to their unique physicochemical properties, low-cost, natural abundance of carbon, non-toxicity and compatibility with large-scale solution synthesis ( Delacou et al, 2017 ). Among these, CNTs are more appealing owing to their large specific surface area, tunable band gap, high optical transmittance in the visible region, competitive electrical conductivity, high charge carrier mobility, excellent flexibility and superior mechanical, thermal and chemical stability ( Khan et al, 2018 ; Oseni et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, how graphene layers are wrapped to form a nanotubular morphology, i.e., the chirality of the tubes, significantly determines the electrical properties of the CNTs ( Alturaif et al, 2014 ). CNTs that consist of a single round roll of graphene with a typical diameter of around 0.4–10 nm are referred to as single-walled CNTs (SWCNTs), whereas those consisting of two or more rolled layers of graphene sheets with a typical diameter of 1.4–100 nm are called double-walled CNTs (DWCNTs) and multiwalled CNTs (MWCNTs), respectively ( Hatton et al, 2008 ; Agbolaghi, 2019b ; Nguyen et al, 2019 ). Currently, SWCNTs have been relatively more studied than MWCNTs owing to the novel properties of SWCNTs, such as their band gap energy that can be tuned from 0 to ∼2 eV, thereby varying their electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%